Pelatihan Penggunaan Aplikasi SIPGAR Bagi Pemuda DAS di Kota Palangka Raya - Andi Tenri Abeng; Garry William Dony; Abdullah; Muharfa; Yudo Harvianto (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
During the Covid-19 pandemic, health factors in the form of maintaining physical fitness are very important. There are many ways to keep your body in shape. The most effective way to maintain physical fitness during the current covid-19 pandemic is to comply with health protocols and get used to exercising so that the body is always in a fit condition. Exercise can be used as an alternative to keep the body fit. Another important thing besides exercising during the current pandemic is checking physical fitness regularly and independently. One way that can be used is the SIPGAR application. An application published by the Ministry of Health of the Republic of Indonesia to check a person's physical fitness independently via Android. The purpose of this activity is that participants get education about physical fitness and can do tests independently through the operation of the SIPGAR application. The method used in this activity is training. The training was conducted for 5 times, with different participants and places. The total number of participants who attended the training was 42 people. Based on the results of the training, there were several problems experienced by the participants including not all participants were able to download applications on the play store and register an account. This is because each participant's cellphone has different specifications. The solution is that participants who successfully register help their friends to register, while still using the identity of the participant who cannot register. After successful registration, then login using their respective cellphones. After the implementation of this activity the youth felt happy, this was because they already had new skills in operating the SIPGAR application. According to the participants, SIPGAR is an application that is easy and accurate to measure a person's physical fitness, besides that the test can also be carried out anywhere and does not require a special place, the most important thing is that the distance reached is 1600 meters. So that the participants will be able to check their physical fitness regularly and independently easily. Another hope that the participants want is training on other applications to support their skills in operating applications regarding self-health checks independently